THE RECEPTION AND HIERARCHY OF TREATIES IN THE INTERNAL LAW OF AMERICAN STATES - Peruana de Derecho Internacional, Sociedad (2020)
In this study the challenges of the American region in terms of reception and regulatoryhierarchy of international treaties in the Internal Law of States are argued. To do this,using the legal-doctrinal analysis method, the theoretical references on treaties and theirrelationship with Internal Law are systematized. Likewise, the current status of thereception and regulatory hierarchy of treaties in the constitutions of 21 American Statesis analyzed.